Development and optimization of erythromycin-loaded lipid-based gel by Taguchi design: In vitro characterization and antimicrobial evaluation (Brazilian Journal of Pharmaceutical Sciences, 2019)
The foremost aim of the current research was to prolong and sustain the release of erythromycin (ERY) by preparing a solid lipid nanoparticles (SLNs)-based gel formulation for the safe and effective treatment of acne. ERY-loaded SLNs were developed, and various process variables were optimized with respect to particle size, zeta potential, and entrapment efficiency using the Taguchi model. The average particle size, PDI, zeta potential, drug entrapment efficiency, and drug loading of optimized SLN (F4) were found to be 176.2±1.82 nm, 0.275±0.011, -34.0±0.84, 73.56%, and 69.74% respectively. The optimized SLN (F4) was successfully incorporated into the carbopol-based hydrogel. The in vitro release of ERY from the SLN gel and plain gel were compared and found to be 90.94% and 87.94% respectively. In vitro study of ERY-loaded SLN gel showed sustained delivery of drug from formulation thus enhancing the antimicrobial activity after 30 hours when compared to ERY plain gel.